2017
DOI: 10.21512/lc.v11i2.1824
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Integrated Reading and Composition (CIRC) and Reading Motivation: Examining The Effect on Students’ Reading Ability

Abstract: This study examined the effect of Cooperative Integrated Reading and Composition (CIRC) and reading motivation on students’ reading ability. The design of the study was the factorial design of experimental research. The research was conducted on one state junior high school in Jepara Municipality under the Ministry of National Education. The independentvariable of this research was teaching strategies which were classified into two; those who used CIRC as the experimental group and those who used conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…This meant that the implementation of CIRC technique in teaching reading comprehension was better than traditional method because the students can help each other. As Mubarok, H & Sofiana, N (2017) in CIRC by having the students work in small groups, it helps the students to accomplish their assignments more quickly. The result of this study showed that the t-score was higher than the t-score of some previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…This meant that the implementation of CIRC technique in teaching reading comprehension was better than traditional method because the students can help each other. As Mubarok, H & Sofiana, N (2017) in CIRC by having the students work in small groups, it helps the students to accomplish their assignments more quickly. The result of this study showed that the t-score was higher than the t-score of some previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…Through this study, the authors felt that the way of thinking and mastery from students in the material discussed should taught more better in other better method. Mubarok and Sofiana (2017) state In cooperative learning, teachers teach students collaborative or social skills so that they can work together more effectively (Larsenfreeman, 2003:159). This is why in cooperative learning, there will be a sharing ideas with other students and students could lead their team discussion.…”
Section: Methodsmentioning
confidence: 99%
“…One of them is the CIRC model that can help students solve and understand the meaning of conceptual issues (Agustinah, 2017). CIRC is a learning model that uses heterogeneous teams to work together to solve a problem (Mubarok & Sofiana, 2017). By involving students reading and writing to find the main ideas, main ideas, or themes in a reading (Varışoğlu, 2016), increasing students' ability to understand a concept and solve abstract problems (Sukiastini, Sadia, & Suastra, 2013).…”
Section: Introductionmentioning
confidence: 99%